2017
DOI: 10.1101/100768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shortwave Infrared Fluorescence Imaging with the Clinically Approved Near-Infrared Dye Indocyanine Green

Abstract: Fluorescence imaging is a method of real-time molecular tracking in vivo that has enabled many clinical technologies. Imaging in the shortwave infrared region (SWIR, 1-2 µm) promises higher contrast, sensitivity, and penetration depths compared to conventional visible and near-infrared (NIR) fluorescence imaging. However, adoption of SWIR imaging in clinical settings has been limited, due in part to the absence of FDA-approved fluorophores with peak emission in the SWIR. Here, we show that commercially availab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 60 publications
0
32
0
Order By: Relevance
“…As we observed, the emission spectrum of NIR‐I dyes did not follow the Franck–Condon principle (i.e., mirror image rule), in which the emission spectra should approximate the mirror image of their absorption spectra . The missing shoulder in the emission spectrum originated from the low detection efficiency of silicon‐based detectors over 900 nm.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…As we observed, the emission spectrum of NIR‐I dyes did not follow the Franck–Condon principle (i.e., mirror image rule), in which the emission spectra should approximate the mirror image of their absorption spectra . The missing shoulder in the emission spectrum originated from the low detection efficiency of silicon‐based detectors over 900 nm.…”
mentioning
confidence: 77%
“…IRDye800CW‐guided surgery trials have been completed with successes, but imaging depth is still limited in the NIR‐I region . Recently, several groups found that some of the clinically approved and commercially available NIR‐I cyanine dyes may function as NIR‐II fluorophores with emission tails extending into the NIR‐II region . However, the mechanism of tail emission was never investigated and it is indeed interesting to establish a general rule to explore conventional NIR‐I dyes with bright NIR‐II tail emission for NIR‐II imaging.…”
mentioning
confidence: 99%
“…The results reported in this manuscript were initially posted by the authors on April 28, 2017, in the online archive, bioRxiv (65). During the manuscript review process, the authors became aware that ICG fluorescence in the SWIR was independently reported by another group in PLoS One on November 9, 2017 (66 …”
Section: Methodsmentioning
confidence: 97%
“…[13] Despite impressive F F values,the quantum efficiencies of the D-A-D chromophores are limited by their low absorption coefficients.R ecently,t he effect of high e values has been highlighted by off-peak SWIR detection of ICG fluorescence surpassing the brightness of early-generation benzobisthiadiazoles. [14] Theh igh absorption coefficient of ICG is mirrored in other members of its chromophore class,t he polymethine dyes.T hese dyes are charged molecules composed of heterocycles linked by am ethine chain ( Figure 1). Nitrogencontaining polymethines (cyanine dyes) with 1-5 methine units span the visible region, while 7-methines,s uch as ICG, reach NIR wavelengths.…”
mentioning
confidence: 99%